2001
DOI: 10.1002/cne.1373
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and physiology of the polyaxonal amacrine cells in the rabbit retina

Abstract: We examined the morphology and physiological response properties of the axon-bearing, long-range amacrine cells in the rabbit retina. These so-called polyaxonal amacrine cells all displayed two distinct systems of processes: (1) a dendritic field composed of highly branched and relatively thick processes and (2) a more extended, often sparsely branched axonal arbor derived from multiple thin axons emitted from the soma or dendritic branches. However, we distinguished six morphological types of polyaxonal cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(119 citation statements)
references
References 31 publications
13
106
0
Order By: Relevance
“…With dendrites in ON and OFF sublamina of the IPL, A1 amacrine cells can receive input from both ON and OFF bipolar cells and should thus inherit centers and surrounds of both types. In previous receptive field studies using small spots and bars of light, an antagonistic surround was found in some rabbit polyaxonal amacrine cells (Volgyi et al, 2001), but not in primate A1 amacrine cells (Stafford & Dacey, 1997). However, these small stimuli are not ideally suited to measure center-surround interactions because of the large size and low gain of the surround.…”
Section: A1 Center-surround Receptive Field Structurementioning
confidence: 96%
See 2 more Smart Citations
“…With dendrites in ON and OFF sublamina of the IPL, A1 amacrine cells can receive input from both ON and OFF bipolar cells and should thus inherit centers and surrounds of both types. In previous receptive field studies using small spots and bars of light, an antagonistic surround was found in some rabbit polyaxonal amacrine cells (Volgyi et al, 2001), but not in primate A1 amacrine cells (Stafford & Dacey, 1997). However, these small stimuli are not ideally suited to measure center-surround interactions because of the large size and low gain of the surround.…”
Section: A1 Center-surround Receptive Field Structurementioning
confidence: 96%
“…The axons are thin, sparsely branching, and along their length are swellings that resemble presynaptic boutons (Fig 1C;Dacey, 1989). Intracellular recordings from A1 amacrine cells, and similar amacrine cells in rabbit retina (Taylor, 1996;Volgyi et al, 2001) revealed that they depolarize transiently and fire action potentials at light onset and offset. The A1 receptive field mapped with small spots and bars is approximately the same size as its dendritic field (Stafford & Dacey, 1997) leading to the hypothesis that A1 cells receive inputs to their dendrites causing depolarization and initiation of action potentials, which then propagate down the axons and across the retina.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…1c). The cells in these clusters could be ganglion cells or, possibly, spiking amacrine cells (Stafford and Dacey, 1997;Volgyi et al, 2001). A ganglion cell can be identified by the presence of a single axon.…”
Section: Functional Classification Of Neuronsmentioning
confidence: 99%
“…For example, our study suggests that gain control over the receptive field center arises from a bipolar cell mechanism, but this mechanism could not explain wide-field gain control signals. Wide-field signals must arise from a distinct amacrine cell mechanism, because only amacrine cells are capable of transmitting signals over such long distances (Stafford and Dacey, 1997;Cook and McReynolds, 1998;Demb et al, 1999;Taylor, 1999;Flores-Herr et al, 2001;Volgyi et al, 2001). These amacrine cells are themselves driven by bipolar cells, and so it is not surprising that the spatial tuning of gain-control mechanisms would be similar over the ganglion cell receptive field center and periphery Victor, 1978, 1979).…”
Section: Two Spatial Mechanisms For Contrast Gain Control In Ganglionmentioning
confidence: 99%